TikTok sebagai Media dalam Membentuk Opini Publik melalui Film Netflix Ice Cold - Michel Adriana; Sinta Paramita (Koneksi, 2026)
The 2016 cyanide coffee murder case was widely discussed in the mass media at the time, with Jessica Wongso as a suspect in the murder of Mirna. This case was brought up again in 2023 through a documentary film entitled "Ice Cold: Murder, Coffee and Jessica Wongso," which aired on Netflix. The film clip video spread through various social media, one of which was TikTok, made the case that caused a stir in 2016 discussed again. Many provided information, views, and opinions to participate in the cyanide coffee case discussion actively. This study uses a qualitative approach with a case study method to analyze the stages of public opinion formation. Using the thinking of the stages of public opinion formation by Cutlip and Center and Erikson and Tedin. The study results show that TikTok is an effective platform for forming public opinion. Through four stages, namely the emergence of issues, there is attention from opinion leaders, discussing solutions, and determining solutions. Through data collection through in-depth interviews, observations, literature studies, and documentation, it is hoped that results that are close to the truth can be obtained. In addition, the results of this study are expected to gain insight into the stages of public opinion formation. Kasus pembunuhan kopi sianida pada tahun 2016 ramai dibahas pada masanya di media massa, dengan Jessica Wongso sebagai tersangka pembunuhan terhadap Mirna. Kasus ini terangkat kembali pada tahun 2023 melalui film dokumenter yang berjudul "Ice Cold: Murder, Coffee and Jessica Wongso" yang tayang di Netflix. Video cuplikan film tersebar melalui berbagai media sosial salah satunya TikTok, membuat kasus yang menghebohkan pada tahun 2016 tersebut kembali dibahas. Banyak yang memberikan informasi, pandangan, dan pendapat mereka untuk turut aktif dalam berpartisipasi diskusi kasus kopi sianida. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus untuk menganalisis tahapan terbentuknya opini publik. Menggunakan pemikiran tahapan pembentukan opini publik Cutlip dan Center serta Erikson dan Tedin. Hasil penelitian menunjukkan bahwa TikTok menjadi platform yang efektif dalam membentuk opini publik. Melalui empat tahapan yaitu munculnya isu, terdapat perhatian opinion leader, mendiskusikan solusi, dan menetapkan solusi. Melalui pengumpulan data dengan wawancara secara mendalam, observasi, studi pustaka dan dokumentasi, diharapkan dapat memperoleh hasil yang mendekati kebenaran. Selain itu, hasil penelitian ini diharapkan dapat mendapatkan wawasan mengenai tahapan pembentukan opini publik.